The Eye of the Storm - Maia, Francisca; Calvão Santos, Gil (Revista Sociedade Portuguesa de Oftalmologia, 2025)
The photograph refers to a 70-year-old man who underwent scleral buckling surgery followed by 360º laser treatment via indirect ophthalmoscopy. This procedure was performed in the USA 20 years ago due to a rhegmatogenous retinal detachment. The current fundoscopic appearance of the retina is presented. His best corrected visual acuity is 20/20, representing the calm after the storm. The image captures a striking fundoscopic appearance rarely encountered in contemporary clinical practice. It presents an almost artistic interpretation of the retina, featuring intricate details that evoke elements of nature, inviting viewers to appreciate the beauty and complexity of the human eye.